Acupuncture versus non-steroidal anti-inflammatory drugs for treatment of chondromalacia patellae: a systematic review and meta-analysis of randomized controlled trials - Lv, Zheng-tao; Li, Zhi-Qiang; Zhou, Xiang; Ma, Wen-Wen; Zhang, Jin-Ming; Chen, An-Min (Forschende Komplementärmedizin, 2016)
This systematic review aims to evaluate the efficacy and safety of acupuncture therapy for treating patients with chondromalacia patellae compared to non-steroidal anti-inflammatory drugs (NSAID). Eight databases including PubMed, EMBASE, CENTRAL, ISI Web of Science, CNKI, Wanfang, VIP, and CBM were searched up to June 2016. Randomized controlled trials (RCT) assessing the efficacy of acupuncture therapy were identified. The patients in experimental groups had to be treated with acupuncture therapy, and the patients in control groups had to be treated with NSAID. The outcome measures included clinical efficacy rates or pain scores. A total of 7 studies met our inclusion criteria. We analyzed the data from these 7 RCT involving 707 participants. All included studies were judged to be at high risk for bias. Compared with NSAID, acupuncture could further improve the clinical efficacy rates (Risk Ratio 2.57; 95% confidence interval (CI) 2.02, 3.27) and pain scores (Mean Difference -1.49; 95% CI -2.37, -0.62). No study reported adverse events associated with acupuncture therapy. Based on the findings in the present review, acupuncture therapy is more effective than NSAID in improving clinical efficacy rates and pain scores. However, these results should be interpreted cautiously due to the poor overall methodological quality of the included trials. Additional studies with large-scale and rigorous experimental design are required.
Gesehen am 20.05.2020